2020
DOI: 10.1002/cmdc.202000092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Telmisartan‐Derived Cell Death Modulators to Circumvent Imatinib Resistance in Chronic Myeloid Leukemia

Abstract: New strategies to eradicate cancer stem cells in chronic myeloid leukemia (CML) include a combination of imatinib with peroxisome proliferator‐activated receptor gamma (PPARγ) ligands. Recently, we identified the partial PPARγ agonist telmisartan as effective sensitizer of resistant K562 CML cells to imatinib treatment. Here, the importance of the heterocyclic core on the cell death‐modulating effects of the telmisartan‐derived lead 4′‐((2‐propyl‐1H‐benzo[d]imidazol‐1‐yl)methyl)‐[1,1′‐biphenyl]‐2‐carboxylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A new therapeutic option could involve a combination of imatinib and chemical compounds capable of exerting antiproliferative effects against K562-resistant leukaemia cells via PPARγ activation. In this direction, sartans, especially telmisartan, have been extensively studied in recent years [ 44 , 45 , 46 ]. This is an intriguing hypothesis that can also have a potential benefit on the comorbidity treatment (HTN, HF) of CML patients as it is known that the therapeutic plasmatic concentration of telmisartan can be assessed during administration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A new therapeutic option could involve a combination of imatinib and chemical compounds capable of exerting antiproliferative effects against K562-resistant leukaemia cells via PPARγ activation. In this direction, sartans, especially telmisartan, have been extensively studied in recent years [ 44 , 45 , 46 ]. This is an intriguing hypothesis that can also have a potential benefit on the comorbidity treatment (HTN, HF) of CML patients as it is known that the therapeutic plasmatic concentration of telmisartan can be assessed during administration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CML cell line K562-R cells was originally described by Hui et al as a Doxorubicin-resistant subclone of the K562 cell line (originally termed as KD225) . K562-R cells are also resistant toward Imatinib, as we described in previous publications. …”
Section: Methodsmentioning
confidence: 99%
“… 50 K562-R cells are also resistant toward Imatinib, as we described in previous publications. 51 54 …”
Section: Methodsmentioning
confidence: 99%
“…Faced with the possibility of therapy-resistant cells to conventional drugs[ 185 ] or other treatment problems, whether by non-remission or progression of the disease and possible adverse effects, new research is looking for alternatives that treat the CML more effectively and improve the life quality of the patients[ 186 ]. The following topics gather some of the most relevant therapeutic strategies in this context.…”
Section: New Perspectives In the CML Treatmentmentioning
confidence: 99%
“…Moreover, it was reported that pioglitazone combined with imatinib increases the apoptotic capacity of tumor cells by a positive regulation of caspase 3, which may mean that a combined therapy with these two drugs can be an alternative for resistant CML treatment[ 186 ]. Telmisartan, a partial agonist of the PPAR-γ, has shown to be effective in circumventing the resistance to imatinib, possibly being more effective than pioglitazone[ 185 ].…”
Section: New Perspectives In the CML Treatmentmentioning
confidence: 99%